Answer:
x = 3, y = 4
Explanation:
First, set the first equation equal to x. Note the equal sign, what you do to one side, you do to the other.
Subtract y from both sides of the equation:
x + y = 7
x + y (-y) = 7 (-y)
x = 7 - y
Next, plug in 7 - y for x in the second equation:
2x + y = 10
2(7 - y) + y = 10
Simplify. First, distribute 2 to all terms within the parenthesis:
2(7 - y) = (2 * 7) + (2 * -y) = 14 - 2y
Next, combine like terms. Like terms are terms with the same amount of the same variables:
14 - 2y + y = 10
14 (-2y + y) = 10
14 - y = 10
Isolate the variable, y. First, subtract 14 from both sides of the equation:
-y + 14 (-14) = 10 (-14)
-y = 10 - 14
-y = -4
Next, isolate the variable, y, by dividing -1 from both sides of the equation:
(-y)/-1 = (-4)/-1
y = -4/-1 = 4
Next, plug in 4 for y in one fo the given equations:
x + y = 7
x + (4) = 7
Isolate the variable, x. Subtract 4 from both sides of the equation:
x + 4 (-4) = 7 (-4)
x = 7 - 4
x = 3
x = 3, y = 4